A Calcified Amorphous Tumor Originating in the Sinus of Valsalva. Issue 5 (May 2016) - Watanabe, Yusuke; Naganuma, Toru; Nakao, Tatsuya; Nakamura, Sunao
Abstract : An 81‐year‐old male with end‐stage renal disease undergoing hemodialysis was admitted to our hospital for congestive heart failure secondary to severe aortic stenosis. Transesophageal echocardiography revealed a 15.3 × 9.9 mm calcified mass in the sinus of Valsalva. The tumor was diagnosed as a calcified amorphous tumor (CAT) by histologic examination. This is the first report of a CAT that originated in the sinus of Valsalva. Mini‐Abstract: An 81‐year‐old male with end‐stage renal disease undergoing hemodialysis was admitted to our hospital for congestive heart failure secondary to severe aortic stenosis. Transesophageal echocardiography revealed a 15.3 × 9.9 mm calcified mass in the sinus of Valsalva. The tumor was diagnosed as a calcified amorphous tumor (CAT) by histologic examination. This is the first report of a CAT that originated in the sinus of Valsalva.